2017
DOI: 10.1108/jmp-01-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

It is your fault! How blame attributions of breach predict employees’ reactions

Abstract: Purpose -Using insights from attributions, planned behavior and fairness theories, this study examines the effect of blame attributions of psychological contract breach on employees' attitudes (affective organizational commitment) and behaviors (OCB). The aim of this study is to understand whether employees' reactions depend on the attributions they make concerning who is responsible for the breach.Design/methodology/approach -Cross-lagged design in which data were collected from 220 employees and their superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“…The severity of PC violation captures “the extent to which employees perceive that the most important promises” have not been fulfilled (Ng & Feldman, 2009, p. 1056). Blame attribution captures the degree of responsibility each party has in the negative disruption event and is related to the intentionality and control of the organization’s action (Costa & Neves, 2017). If the focal individual finds the coworker’s PC violation is not severe and/or that the coworker is to blame for the organization’s action, they will be motivated to “avoid” and do nothing (O’Reilly & Aquino, 2011).…”
Section: Triggering the Sensemaking Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of PC violation captures “the extent to which employees perceive that the most important promises” have not been fulfilled (Ng & Feldman, 2009, p. 1056). Blame attribution captures the degree of responsibility each party has in the negative disruption event and is related to the intentionality and control of the organization’s action (Costa & Neves, 2017). If the focal individual finds the coworker’s PC violation is not severe and/or that the coworker is to blame for the organization’s action, they will be motivated to “avoid” and do nothing (O’Reilly & Aquino, 2011).…”
Section: Triggering the Sensemaking Processmentioning
confidence: 99%
“…In support of this argument, the fairness literature states that when the organization does not have control over the situation (e.g., PC violation), individuals tend to be tolerant (Folger & Cropanzano, 2001). Prior research has shown that when individuals blame the context for PC violation, no changes occur in the perceptions of the employment relationship in terms of their organizational commitment (Costa & Neves, 2017). On the other hand, if the focal individual finds the coworker’s PC violation is severe and the organization is to blame (the coworker’s PC violation was intentional), they will feel motivated to engage in active sensemaking. Proposition 4: An observed or coworker-disclosed PC violation that is deemed severe and intentional by the focal individual is more likely to trigger the focal individual’s sensemaking process.…”
Section: Triggering the Sensemaking Processmentioning
confidence: 99%
“…Third, in response to calls to apply contingency approaches to the outcomes of negative psychological contract situations (e.g. Arshad, 2016; Biswas, 2016; Costa and Neves, 2017; Restubog et al , 2015), this study proposes that employees’ beliefs about the nature of their psychological contract may influence how much job strain they experience due to felt violations, which then informs their job performance. Consistent with COR theory, the extent to which the nature of their psychological contract intensifies the resource loss caused by a sense of organizational betrayal should enhance the experience of job-related anxiety in response to this negative situation (Priesemuth and Taylor, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In a moment of crisis and segregation, where ethnic groups are more salient, the perception of discrimination toward immigrants may have an impact on immigrant workers’ OCB. Perceived discrimination runs counter to the clause of dignified treatment that defends the psychological contract, and recent studies show that the attributions of blame for the breach of this contract have a negative impact on OCB [8].…”
Section: Introductionmentioning
confidence: 99%
“…Motivational orientations can be defined as the individual’s guide for the interpretation of knowledge and the production of cognitions, emotions, and behaviors when facing tasks [9]. The literature has pointed out the existence of two types of motivational orientations, performance orientations and learning orientations, which have been identified as two distinct dimensions [8]. Learning orientation is characterized by the search for perfection in new situations and the acquisition of skills.…”
Section: Introductionmentioning
confidence: 99%